Fear, misinformation, and pharmaceutical messianism in the promotion of compounded bioidentical hormone therapy - Kauffman, Robert P.; MacLaughlin, Eric J.; Courtney, Lindsay A.; Vineyard, David D. (Frontiers in Reproductive Health, 2024)
Compounded bioidentical hormone therapy (cBHT) for menopausal symptoms maintains popularity in western countries despite the availability of hormone products in different formulations and dosages produced by pharmaceutical companies with federal oversight. Akin to many populist therapeutic trends in the history of medicine, cBHT advocates tend to capitalize on consumer fears about existing FDA-approved hormone treatments. Unsubstantiated, exaggerated, or outright false claims are commonplace in promoting cBHT. Given these elements, the basic elements of pharmaceutical messianism continue to drive the cBHT movement.